Measuring Economic Growth in New Zealand - Peter Mawson (New Zealand Government, The Treasury, 2002)
This paper examines New Zealand's ranking in the OECD based on real GDP per capita. The fall in ranking experienced by New Zealand implies that real GDP per capita growth in New Zealand has been relatively poor in comparison to other OECD countries. The paper examines the history of New Zealand's growth rate and explores the differences between various techniques for measuring average growth rates. The approaches are all shown to be variants of the average annual growth rate but differ in terms of the weighting structure used. Ultimately, the most appropriate technique depends on the underlying data generating process. The implications of data construction techniques for measured growth rates are discussed and differences between the growth rates obtained from different data sources are illustrated. The paper also illustrates the sensitivity of New Zealand growth rates to the sample period chosen.
Keywords: O47; C10; 330; Economic Growth; Measuring Growth; International Comparisons